2011
DOI: 10.2473/journalofmmij.127.182
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashallow Underground Imaging System For Detecting Buried Object Using Giant-Magnetostriciton Vibrator

Abstract: Recently, Water and gas pipes are developed frequently because of the increased urban population. When the underground piping is constructed, drawings and signs are needed to drill the ground. However, underground pipings and other buried objects are often buried in different locationscompared with drawings. Underground pipings, the rock and the gravel interfere with construction. It is necessary to avoid this situation. To determine the construction of underground pipes, the non-destructive imaging method pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Propagation velocity of sand in previous studies is shown. [28][29][30][31] When sand is assumed to be solid or liquid, propagation velocity is shown. 26) Ultrasound irradiation can be applied to SAGD, it is effective to propagate widely.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Propagation velocity of sand in previous studies is shown. [28][29][30][31] When sand is assumed to be solid or liquid, propagation velocity is shown. 26) Ultrasound irradiation can be applied to SAGD, it is effective to propagate widely.…”
Section: Experimental Methodsmentioning
confidence: 99%